1993
DOI: 10.1677/joe.0.1360297
|View full text |Cite
|
Sign up to set email alerts
|

Receptor binding of insulin-like growth factor-I to mammary microsomes from non-pregnant, pregnant and lactating sheep

Abstract: Sucrose density centrifugation was used to prepare a partially purified membrane fraction from the mammary glands of non-pregnant, pregnant and lactating sheep. The binding of 125I-labelled insulin-like growth factor-I (IGF-I) was dependent on membrane protein concentration, pH, time and temperature. The binding showed the characteristics of a type-1 IGF receptor, being displaced by IGF-I (median effective dose (ED50) 0.55 nmol/l), less effectively by IGF-II (ED50 8.8 nmol/l) and least effectively by insulin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
(35 reference statements)
1
1
0
Order By: Relevance
“…5). This is similar to the reported size for 1-5I-IGF-I complexed to the -subunit of the type 1 receptor (Massague & Czech 1982, Winder et al 1993. These data support the view that the 125I-IGF-I binding demon¬ strated by histological autoradiography is to the type 1 receptor and that it is the type 1 receptor in connective tissue which is nutritionally regulated, rather than a membrane-associated IGF-binding protein.…”
Section: Resultssupporting
confidence: 87%
“…5). This is similar to the reported size for 1-5I-IGF-I complexed to the -subunit of the type 1 receptor (Massague & Czech 1982, Winder et al 1993. These data support the view that the 125I-IGF-I binding demon¬ strated by histological autoradiography is to the type 1 receptor and that it is the type 1 receptor in connective tissue which is nutritionally regulated, rather than a membrane-associated IGF-binding protein.…”
Section: Resultssupporting
confidence: 87%
“…Microsomes were prepared by homogenization and differential centrifugation (Winder et al 1993) from the mammary glands of bromocriptine-treated New Zealand White rabbits in early lactation and the livers of Poll-Dorset ewes and were freeze dried (Parke & Forsyth 1975). Displacement studies using unlabelled ovine PL, ovine prolactin (NIH-P-S-12, 35 i.u./mg) and bovine GH (NIH-B-GH-2, 1·5 i.u./mg) confirmed that rabbit mammary gland contains predominantly lactogenic receptors (displaced by prolactin and ovine PL, but not by bovine GH, Kelly et al 1976), while sheep liver contains mainly somatotrophic receptors (displaced by bovine GH and ovine PL, but not by prolactin, Brier et al 1994).…”
Section: Tissue Binding Studiesmentioning
confidence: 99%